2016
DOI: 10.7554/elife.09100
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB oscillations translate into functionally related patterns of gene expression

Abstract: Several transcription factors (TFs) oscillate, periodically relocating between the cytoplasm and the nucleus. NF-κB, which plays key roles in inflammation and cancer, displays oscillations whose biological advantage remains unclear. Recent work indicated that NF-κB displays sustained oscillations that can be entrained, that is, reach a persistent synchronized state through small periodic perturbations. We show here that for our GFP-p65 knock-in cells NF-κB behaves as a damped oscillator able to synchronize to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
208
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(225 citation statements)
references
References 69 publications
(189 reference statements)
17
208
0
Order By: Relevance
“…Transcriptome profiling of cells synchronized with this pulsatile TNF input, demonstrated that while genes encoding unstable mRNAs exhibited pulsatile expression dynamics, genes with long-lived mRNAs showed instead a steady concentration or slow increase. Intriguingly, these two gene sets are functionally distinct; pulsatile genes principally encode chemokines and their receptors and the others encode innate immune response and extracellular matrix remodeling genes [35]. …”
Section: Imaging and Fluidics To Measure Nf-κb Pathway Signaling And mentioning
confidence: 99%
“…Transcriptome profiling of cells synchronized with this pulsatile TNF input, demonstrated that while genes encoding unstable mRNAs exhibited pulsatile expression dynamics, genes with long-lived mRNAs showed instead a steady concentration or slow increase. Intriguingly, these two gene sets are functionally distinct; pulsatile genes principally encode chemokines and their receptors and the others encode innate immune response and extracellular matrix remodeling genes [35]. …”
Section: Imaging and Fluidics To Measure Nf-κb Pathway Signaling And mentioning
confidence: 99%
“…5(d)]. Now we turn to investigating how molecular stripping changes the stochastic behavior of the switch when the broadcasting system displays self-sustained pulsatile behavior [31]. Keeping the degradation rate α(t > 0) = 0.25 min −1 constant in the simulation leads to oscillations of the nuclear NFκB with a period of ∼2 h [37] consistent with the commonly adopted experimental setup [29,30].…”
Section: Active Regulation Of Bound Transcription Factors Resolvmentioning
confidence: 93%
“…Binding to the promoter site initiates the synthesis of IκB which then repeats the cycle as long as the external stimulation is present. Due to long delayed negative feedback by IκB, the network shows undamped oscillations of NFκB/IκB at the single cell level under constant stimulation [29][30][31]. The removal of stimulation is followed by clearance of NFκB from the nucleus and return to the steady state where all of the NFκB is retained in cytoplasm by the IκB until the encounter of a new signal.…”
Section: The Nfκb/iκb-dna Broadcasting Networkmentioning
confidence: 99%
See 2 more Smart Citations